Talk Ain't Cheap: Political CSR and the Challenges of Corporate Deliberation. Issue 2 (20th March 2017) - Sabadoz, Cameron; Singer, Abraham
ABSTRACT: Deliberative democratic theory, commonly used to explore questions of "political" corporate social responsibility (PCSR), has become prominent in the literature. This theory has been challenged previously for being overly sanguine about firm profit imperatives, but left unexamined is whether corporate contexts are appropriate contexts for deliberative theory in the first place. We explore this question using the case of Starbucks' "Race Together" campaign to show that significant challenges exist to corporate deliberation, even in cases featuring genuinely committed firms. We return to the underlying social theory to show that this is not an isolated case: for-profit firms are predictably hostile contexts for deliberation, and significant normative and strategic problems can be expected should deliberative theory be imported uncritically to corporate contexts. We close with recent advances in deliberative democratic theory that might help update the PCSR project, and accommodate the application of deliberation to the corporate context, albeit with significant alterations.